2014
DOI: 10.1111/nph.13009
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling the effect of arsenic on the model Medicago–Ensifer interaction: a transcriptomic meta‐analysis

Abstract: SummaryThe genetic regulation underlying the effect of arsenic (As(III)) on the model symbiosis Medicago-Ensifer was investigated using a combination of physiological (split-roots), microscopy and genetic (microarrays, qRT-PCR and composite plants) tools.Nodulation was very sensitive to As(III) (median inhibitory dose (ID50) = 20 lM). The effect on root elongation and on nodulation was local (nonsystemic). A battery of stress (salt, drought, heat shock, metals, etc.)-related genes were induced. Glutathione pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(10 citation statements)
references
References 134 publications
0
10
0
Order By: Relevance
“…Interestingly, previous studies indicated that these strains exhibit traits of interest for phytoextraction. Thus, species of the Ensifer genus were found in association with Medicago plants, where inoculated plants exhibited a reduction in the stress response, thereby indicating the protective effect of As-tolerant rhizobia (41). It has been demonstrated that Rhizobium species promoted plant growth in Lolium multiflorum (Lam.)…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, previous studies indicated that these strains exhibit traits of interest for phytoextraction. Thus, species of the Ensifer genus were found in association with Medicago plants, where inoculated plants exhibited a reduction in the stress response, thereby indicating the protective effect of As-tolerant rhizobia (41). It has been demonstrated that Rhizobium species promoted plant growth in Lolium multiflorum (Lam.)…”
Section: Discussionmentioning
confidence: 99%
“…Sinorbizobium ) medicae MA11. 174 This study identified the adaptive responses of the bacterial symbiont to arsenic exposure. This metatranscriptomic approach will be useful to study how microbes regulate their genes to adapt to the changes in environmental conditions, particularly arsenic concentrations.…”
Section: Understanding Biogeochemical Arsenic Cycling By Applicatimentioning
confidence: 99%
“…For example, a microarray analysis shows that approximately 14% of the whole Herminiimonas asoxydans genome is significantly affected by 15 min of As(III) exposure ( Cleiss-Arnold et al, 2010 ). Though numerous studies have explored the profiling analysis of the whole organism’s metabolic pathways in response to As stress in plants and animals ( Zheng et al, 2005 ; Yu et al, 2012 ; Lafuente et al, 2014 ); the biochemical and molecular mechanisms of As-induced cytotoxicity in bacteria and bacterial responses to that cytotoxicity remain largely unknown. However, understanding the As resistance of bacteria is crucial because of the increasing As contamination in the environment.…”
Section: Introductionmentioning
confidence: 99%